Effect of calcination temperature and time on waste heterogeneous catalysts for biodiesel production - Sulaiman, Sarina; Majid, Siti Rohana (Trans Tech Publications Ltd, 2016)
This paper studies the effect of calcination time and temperature of mixed waste catalyst for optimization of FAME yield. Fish bone and mixture of coconut waste and eggshells were used to catalyzed the transesterification process. The parameter was tested on different calcination condition and the result shows that the optimum condition was achieved at condition 800˚C, 2 hours was 80.3 wt% of FAME yield for mixed coconut waste and eggshells and 85 wt% were obtained at 900˚C for fish bone catalyst at 225 rpm, 12:1 methanol to oil ratio and amount of catalyst, 3wt%. It can be concluded that waste heterogeneous catalyst exhibits as a cheaper substitute to the homogenous catalyst.